Service Industries and Regions Growth, Location and Regional Effects - Cuadrado-Roura, Juan R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The service sector in most advanced economies accounts for up to seventy percent of employment and GDP and, given its growing importance, has received much research attention over the last two decades. However, not very much attention has been paid to the relationship between this sector and both its terrritorial impact and regional effects. The main objective of this book is to offer a comprehensive approach to these aspects, focusing particularly on the location factors of service industries and the importance of some specific services, such as business services and knowledge and information services. The contributions have been prepared by well-known experts in the field from a wide number of countries. The focus of all contributions is not only on theoretical aspects, but also provides empirical analyses on specific countries and topics such as the geographical concentration, globalization impacts, foreign direct investments, and innovation.
Introduction -- Part I: Service Industries: Growth Factors, Globalization and Innovation -- Part II: Regional Aspects of FDI in Services, Export Decisions, Productivity and Employment -- Part III: Location of Service Industries: Cities, Internationalization, the Case of Some Specific Activities and Regional Development Policies.
Keywords: Economics; Geography; Industrial organization (Economic theory).; Regional economics; Economics/Management Science; Regional/Spatial Science; Economic Geography; Industrial Organization